DEVELOPMENT OF POP-UP BOOK LEARNING MEDIA IN MATHEMATICS ON PLANGEOMETRY MATERIAL FOR GRADE III STUDENTS AT SD NEGERI 064965 MEDAN - Anzelina Br Sinulingga; Lilik Hidayat Pulungan (Journal of Innovation in Research, Education and Culture (JIREC), 2026)
This study aims to: (1) determine the product of Pop-Up Book learning media on plane geometry material, (2) determine the validity level of the media, and (3) determine the practicality level of the media. The method used in this study is Research and Development (R&D). The development model applied is the 4D model, which consists of four stages: (1) Define, (2) Design, (3) Development, and (4) Dissemination, introduced by Thiagarajan. This study produced a Pop-Up Book learning media for multiplication in elementary schools. Based on the validation results, the average scores were 91% from material experts, 93% from media experts, and 96% from language experts, indicating that the learning media meets the criteria of “very valid.” The practicality results showed that the teacher response reached 92% and the student response reached 95%, indicating that the learning media meets the criteria of “very practical.” Based on these results, it can be concluded that the Pop-Up Book learning media is highly valid/feasible and very practical for use in the learning process.